2012
DOI: 10.3126/jnps.v32i2.5995
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies at Birth: A Hospital Based Study in UAE

Abstract: Introduction: It is widely acknowledged that congenital anomalies heavily contribute to infant morbidity and mortality worldwide, with an estimated 9 million infants (7% of all births) born annually having a serious congenital anomaly that result in death or lifelong disability. The objective of our study was to estimate the frequency of congenital anomalies at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In the present study, the most common malformations were observed in the genitourinary system (24.2%), followed by the musculoskeletal system (21.2%) and cardiovascular system (18.2%). A similar study by Arya Singhe L, et al 13 showed that the most common congenital malformation involved the genitourinary system, followed by the musculoskeletal system. Likewise, a study by Malla BK 5 showed that the most common system involved in congenital malformations were central nervous system, followed by musculoskeletal, gastrointestinal, genitourinary, and sense organ system.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, the most common malformations were observed in the genitourinary system (24.2%), followed by the musculoskeletal system (21.2%) and cardiovascular system (18.2%). A similar study by Arya Singhe L, et al 13 showed that the most common congenital malformation involved the genitourinary system, followed by the musculoskeletal system. Likewise, a study by Malla BK 5 showed that the most common system involved in congenital malformations were central nervous system, followed by musculoskeletal, gastrointestinal, genitourinary, and sense organ system.…”
Section: Discussionmentioning
confidence: 68%
“…In the studies conducted in maternity hospital and western Regional hospital, Pokhara, malformations among the male live births was slightly higher than the female live births. In the study of Swain 11 reported higher incidence rate of 1.2% in his study in India, as higher as in Egypt 4 2.5%, New York 10 5.1% and in Abu Dhabi 12 6.9% were also reported.…”
Section: Discussionmentioning
confidence: 81%
“…The 2006 March of Dimes report ranks the UAE 6th in the world in terms of prevalence of genetic and partially genetic birth defects ( Christianson et al, 2006 ). Hospital based studies reported that 0.31% of live births had neonatally lethal anomalies while 6.9% had congenital anomalies ( Dawodu et al, 2005 ; Aryasinghe et al, 2012 ). These high rates are largely due to the tribal nature of Emirati culture with an elevated consanguinity rate (50%) and the presence of isolated populations with increased levels of inbreeding.…”
Section: Introductionmentioning
confidence: 99%